2003
DOI: 10.1074/jbc.c200651200
|View full text |Cite
|
Sign up to set email alerts
|

Nod2 Is a General Sensor of Peptidoglycan through Muramyl Dipeptide (MDP) Detection

Abstract: Nod2 activates the NF-B pathway following intracellular stimulation by bacterial products. Recently, mutations in Nod2 have been shown to be associated with Crohn's disease, suggesting a role for bacteria-host interactions in the etiology of this disorder. We show here that Nod2 is a general sensor of peptidoglycan through the recognition of muramyl dipeptide (MDP), the minimal bioactive peptidoglycan motif common to all bacteria. Moreover, the 3020insC frameshift mutation, the most frequent Nod2 variant assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
1,668
2
21

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,116 publications
(1,744 citation statements)
references
References 27 publications
30
1,668
2
21
Order By: Relevance
“…The functional relevance of TLR4 mutations may be less secure following the identification of MDP as the ligand for NOD2/CARD15. 30 Although previous data from Germany have implicated the CD14 promoter variant in disease susceptibility, we could not confirm the T-159C mutation as a susceptibility gene for CD in our population. It is of some interest that this SNP is associated with earlier age of onset, as this variant maps to the IBD5 region, which in an early study was only of genome-wide significance in families with early-onset disease.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The functional relevance of TLR4 mutations may be less secure following the identification of MDP as the ligand for NOD2/CARD15. 30 Although previous data from Germany have implicated the CD14 promoter variant in disease susceptibility, we could not confirm the T-159C mutation as a susceptibility gene for CD in our population. It is of some interest that this SNP is associated with earlier age of onset, as this variant maps to the IBD5 region, which in an early study was only of genome-wide significance in families with early-onset disease.…”
Section: Discussioncontrasting
confidence: 71%
“…The Irish CD group comprised 113 patients (77 females and 36 males) with a median age at diagnosis of 27.5 years (IQR [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. This corresponded to 38 patients diagnosed before the age of 40 years (A1) and 21 diagnosed after the age of 40 years (A2).…”
Section: Irish Patient Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…a receptor of bacterial peptidoglycans [35] and only recently we demonstrated its role in the recognition of mycobacteria [36,37]. It has also been recently shown that common polymorphisms of NOD2 are strongly associated with TB in African-American patients [38].…”
Section: Discussionmentioning
confidence: 88%
“…28 Muramyl dipeptide, the minimal essential structure of bacterial peptidoglycan carried on bacterial cell walls, is specifically recognised by the LRR domain. 29 Binding of bacteria modifies the inflammatory response within the cell by an effect on nuclear factor-kB activity. 30 Expression of NOD2/CARD15 is found within intestinal epithelial cells with highest concentrations of NOD2/ CARD15 mRNA found in Paneth cells.…”
Section: Introductionmentioning
confidence: 99%